Mono No Aware Dalam Manga Naruto Karya Masashi Kishimoto - Raihan Khairunnisa, Mirda; Wirian, Ni Made; Damayanti, Silvia (Humanis; Volume 17. No. 2. Nopember 2016, 2016)
The title of thi s research is “Mono no Aware in Comic entitled Naruto by Masashi Kishimoto ” . Th is research aims to analyz e the depiction of mono no aware and the character’s reaction about the depiction of mono no aware in a comic entitled Naruto by Masashi Kishimoto. The theories that are used for analyzing are theory of mono no aware by Norinaga (1926) and theory of comic by McCloud (2006). The results of this research are the depiction of mono no aware in comic entitled Naruto by Masashi Kishimoto are depicted by event between people who show deep emotions and nature conditions. The character’s reaction about the depiction of mono no aware are negative and positive.